EPIDEMIOLOGY, RISK FACTORS AND PATHOMORPHOLOGICAL FEATURES OF MAMMARY TUMORS IN CATS - Dyulger, G.P.; Dyulger, P.G.; Alikhanov, O.; Sedletskaya, E.S.; Latynina, E.S.; Obukhova, M.E.; Leontieva, I.L.; Bychkov, V.S.; Baimukanov, D.A. (Scientific Journal of Pedagogy and Economics, 2020)
Mammary tumors (MT) are the 3rd most common neoplasm in cats. The incidence rate is significantly influenced by gender, age, breed, ovarian status, and the use of progestin-based contraceptives. MTs are a group of neoplasms that is heterogeneous in terms of tissue belonging, histological structure, and biological behavior. Malignant tumors are most frequent and compile from 80% to 96% of all tumors and tumor-like mammary lesions. Mammary cancer (MC) prevails, accounting for 91.4% of all cases of malignant tumors. Invasive breast cancer is much more common than carcinoma in situ. Among histological types of breast cancer, cribriform, solid, and tubulopapillary carcinomas predominate; mucous, tubular, and papillary carcinomas are less common.